Social Media Reveals Potential Threat of Crayfish Trap to Birds - Chao Gong; Wei Hu; Taiyu Chen; Zhenqi Wang; Changhu Lu (Diversity)
Fishery bycatch is a significant threat to biodiversity, with birds being frequent casualties. Current research mainly focuses on seabird bycatch in large-scale marine fisheries, while bird bycatch in inland freshwater areas remains poorly understood. Crayfish traps are extensively used in China’s freshwater environments, but their ecological impacts on birds are overlooked due to monitoring difficulties. Through iEcology approaches, we collected and analyzed 146 bird bycatch incidents in crayfish traps from Chinese social media platforms between September 2010 and December 2023. The results revealed 420 identified birds from 62 species (11 orders, 24 families), predominantly omnivorous and carnivorous, while 106 individuals could not be identified. Cases were concentrated in the middle and lower reaches of the Yangtze River, showing significant positive correlations with water area ratio and aquaculture production (p < 0.001). During fishing seasons, the number of cases, species, and individuals were significantly higher (p < 0.001), though mortality rates increased in off seasons. The middle and lower reaches of the Yangtze River are main production areas of red swamp crayfish (Procambarus clarkii) and Chinese mitten crab (Eriocheir sinensis), where intensive use of crayfish traps may increase bird bycatch risk. Despite existing regulations, systematic supervision is needed to minimize ecosystem impacts.